2011
DOI: 10.3139/146.110585
|View full text |Cite
|
Sign up to set email alerts
|

Role of microalloying elements in the microstructure of hot rolled steels

Abstract: Role of microalloying elements in the microstructure of hot rolled steelsA comparative study of some of the most important effects of the diverse microalloying elements on austenite and ferrite microstructure of hot rolled microalloyed steels is carried out. The values of different aspects such as pinning and driving forces, size of precipitates, activation energies or diffusion coefficients are discussed. Titanium is the most effective element to control grain growth at high reheating temperatures and a weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Alloying elements of the steel have an important effect on static recrystallization because recrystallization and grain growth activation energy are changed with respect to chemical composition [38,39]. An analytical model has to cover different steel categories and their chemical composition to reduce the prediction error.…”
Section: Models and Methodologymentioning
confidence: 99%
“…Alloying elements of the steel have an important effect on static recrystallization because recrystallization and grain growth activation energy are changed with respect to chemical composition [38,39]. An analytical model has to cover different steel categories and their chemical composition to reduce the prediction error.…”
Section: Models and Methodologymentioning
confidence: 99%
“…Mn diffuses extremely slowly in austenite with a diffusion constant of m 2 s −1 at 636 C [68]. This is compared to Mn in ferrite with a diffusion constant of m 2 s −1 also at 636 C [68] or another substitutional element Al which has a diffusion constant on the order of m 2 s −1 at 600 C in austenite [69], both of which are nearly two orders of magnitude faster than Mn. Mn partitioning is therefore a common challenge in multi-phase 3Gen AHSS [70].…”
Section: Metallurgy Of Medium Mn Steelsmentioning
confidence: 99%
“…Apart from this, ample amount of studies can be found in the literature regarding the hot deformation behavior of microalloyed steels [13][14][15][16][17][18][19][20][21][22]. Although the precipitating phases are different in nature in Ni-base superalloys, these studies are particularly interesting from the perspective of current study because both 718Plus and microalloyed steels (especially with Nb) show similar precipitation -hot deformation behavior.…”
Section: Introductionmentioning
confidence: 97%